Analysis of quality data a tool for observing the attack in beach handball - Morillo, J. P.; Hernandez-Mendo, A. (Revista Iberoamericana de Psicologia del Ejercicio y el Deporte, 2015)
Analysis of Quality Data used in the construction of an observation tool designed ad hoc is presented. It is a mixed system of field formats and categories systems of mutually exclusive and exhaustive (E/ME) which aims to codify the attack phase of beach handball. They are used as criteria: minute marker, end zone and who end. 12 observations were coded absolute male national teams. The analysis was performed using the consensus agreement (qualitative approach to data quality), producing a file error detection, calculating the Cohen Kappa index, the correlation coefficients of Kendall Tau b, Pearson and Spearman; and Generalizability analysis. The results of the correlation coefficients exhibit a minimum rate of 0.993, the Kappa Cohen indices are at 0.917 and generalizability indices are optimal. These results ensure that the observation tool, as well as having a good fit, allows you to record with confidence and precision.